2018
DOI: 10.1097/mph.0000000000001009
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome: Risk Factors and Impact on the Outcome in Children With Acute Lymphoblastic Leukemia Treated With Nordic Protocols

Abstract: Posterior reversible encephalopathy syndrome (PRES) in children with acute lymphoblastic leukemia has been increasingly recognized as a clinicoradiological entity. Our aim was to describe the incidence of PRES in pediatric patients with ALL, identify its risk factors, and examine its prognostic importance. For this research, we conducted a systematic, retrospective review of the patient records in a population-based series of children with acute lymphoblastic leukemia (n=643) treated in Finland from 1992 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 39 publications
1
26
1
1
Order By: Relevance
“…Additionally, the two new findings suggested that CNS involvement/leukemia was related to a significantly higher risk of PRES as compared with no CNS involvement/ leukemia. Tcell leukemia had a higher risk of PRES in pediatric hematologic disease after conducting chemotherapy (2,20). The study on the risk factors of the incidence between PRES related to T-cell leukemia and CNS leukemia/involvement in our analysis showed that the risk of PRES in children with T-cell leukemia significantly increases.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Additionally, the two new findings suggested that CNS involvement/leukemia was related to a significantly higher risk of PRES as compared with no CNS involvement/ leukemia. Tcell leukemia had a higher risk of PRES in pediatric hematologic disease after conducting chemotherapy (2,20). The study on the risk factors of the incidence between PRES related to T-cell leukemia and CNS leukemia/involvement in our analysis showed that the risk of PRES in children with T-cell leukemia significantly increases.…”
Section: Discussionmentioning
confidence: 64%
“…Although numerous studies have investigated PRES continuously, the specific risk factors of developing PRES in children remain unclear, since PRES occurs before or during acute neurological symptoms, such as seizures, mental impairment, visual disturbance, headache, vomiting, and other risk factors associated with progressing long-term neurological disorder or death. Of the six studies included (2,8,18,20,25,27), we found that data on sex (male), age group ≥10 years (or 10.0-20.0 years), acute GVHD, hypertension, immunodeficiency, sickle cell disease, T-cell leukemia, CNS leukemia/involvement are associated with poor outcomes or prognoses of patients with PRES and is a limitation on children. In this meta-analysis, a significantly higher incidence of risk was found in female children than in male children in the oncologic age groups of PRES.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations